Determinants of Islamic Bank’s Selection Criteria in Developing Economy - Sidra Gazali; Umm-e-Habiba; Hira Idress; Shahab Aziz; Asma Zeeshan; Muhammad Kamran Khan (International Journal of Business and Economic Affairs, 2023)
The purpose of this study is to examine the determinants of the selection criteria of Islamic banks in the developing market of Pakistan. The dependent variable is the bank’s selection criteria and other explanatory factors include consumer demographics, attitude and preferences. The data collection method used in this study is qualitative and based on a questionnaire from consumers using banking services in Pakistan. Alpha test, structural equation model SEM and linear model are used as tools for analyzing the data. The results of the study show that all factors have a positive significant association with the bank selection criteria of consumers in Pakistan. We found that location and availability of ATMs, behavior of bank staff, efficiency of services and low service fees have a positive impact on bank selection decisions. Taken together, these results suggest that banking service choices are strongly influenced by consumer demographics, attitudes, and preferences. Therefore, bank management must pay attention to these factors to improve customer satisfaction and expand the customer base. The study is limited to the less developed market of Pakistan with different culture and values of Pakistan and its consumer selection criteria. The study has implications for students, consumers, researchers and policy makers in the banking sector. In the future, the study can be expanded by adding moderating or mediating factor influences.